INTEGRATION OF ASTA CITA VALUES IN THE DEVELOPMENT OF PESANTREN BASED LIVESTOCK BUSINESSES - Supadi, Supadi; Sudarsana, Sudarsana (AGRONIMAL: Jurnal Ilmiah Pertanian dan Peternakan, 2026)
This study aims to analyze the integration of Asta Cita values in the development of pesantren-based livestock enterprises and their contribution to institutional economic independence and student empowerment. The research was conducted at Pondok Pesantren Nurul Islam Tengaran using a qualitative approach through in-depth interviews, participant observation, and document analysis. The findings reveal that values of economic self-reliance, collective participation, equitable benefit distribution, and sustainability are internalized in livestock management practices through deliberative decision-making, active student involvement, and collective profit allocation. The integration of these values contributes to diversified institutional funding sources, enhanced entrepreneurial capacity among students, and strengthened social capital within the pesantren. However, challenges remain in managerial capacity, capital access, and leadership regeneration. This study highlights that pesantren-based livestock enterprises can serve as a practical model for implementing people-centered economic development within a sustainable national development framework.